KONSEP NUSYU - Wahyuni, Sri (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2008)
The concept of wife’s nusyu>z to husband formulated previous scholars as disobedience wife to husband like out of the house without the husband's permission need to be revisited. Nusyu>z concept in Islamic law does not actually legalize all forms of violence to wives. Beating of wives in an-Nisa '(4): 34 should be interpreted as an act to give a lesson, not to hurt even do violence. Moreover, beating at the verse should not be to injure members of his wife's body. Meanwhile, the act of a husband who beat his wife to injury or other forms of violence committed by husbands to wives, can be expressed as nusyu>z husband to wife. In this paper, the authors attempt to reinterpret the concepts of nusyu>z and the beating as effort to minimize domestic violence.Konsep nusyuz isteri terhadap suami yang dirumuskan ulama terdahulu sebagai ’ketidaktaatan isteri terhadap suami’ seperti keluar rumah tanpa izin suami dan lain sebagainya kiranya perlu ditinjau kembali. Konsep nusyuz dalam hukum Islam sebenarnya tidak melegalkan segala bentuk kekerasan terhadap isteri. Pemukulan terhadap isteri dalam an-Nisa’ (4): 34 hendaknya dimaknai sebagai tindakan untuk memberi pelajaran, bukan untuk menyakiti bahkan berbuat kekerasan. Apalagi pemukulan yang dimaksud ayat tersebut tidak boleh sampai melukai anggota tubuh isteri. Sementara itu, tindakan suami yang memukul isterinya hingga luka atau bentuk kekerasan lain yang dilakukan oleh suami terhadap isteri maka dapat dinyatakan sebagai nusyuz suami terhadap isteri. Dalam tulisan ini, penulis mencoba melakukan reinterpretasi terhadap konsep nusyuz dan pemukulan tersebut sebagai upaya minimalisasi tindak kekerasan dalam rumah tangga.